Role of Solar Power in Sustainable Development of India - Moumita Sadhu; Suprava Chakraborty; Niladri Das; Pradip Kumar Sadhu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Bulk group of rural households, dependency on insufficient and poor quality energy sources are the features of Indian energy consumption pattern. Sustainability is the move towards the growth and development of India. Solar Energy is one of the renowned sectors to support the sustainability of India. Solar energy has giant potential in India due to its position in tropical belt. This paper deals with the new innovative applications of solar energy for sustainable development of India. Solar application in transportation, architecture, car parking, restaurants, lighting, mobile charging etc are described for sustainable development. The paper includes the existing applications of solar energy, the current status of solar energy in India, challenges in the progress of solar energy and concludes with some solutions to promote solar energy. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7668